Search for resonant pair production of Higgs bosons decaying to bottom quark-antiquark pairs in proton-proton collisions at 13 TeV - (:unkn) unknown (SPRINGER, 2018)
A search for a narrow-width resonance decaying into two Higgs bosons, each decaying into a bottom quark-antiquark pair, is presented. The search is performed using proton-proton collision data corresponding to an integrated luminosity of 35.9 fb(-1) at root s = 13 TeV recorded by the CMS detector at the LHC. No evidence for such a signal is observed. Upper limits are set on the product of the production cross section for the resonance and the branching fraction for the selected decay mode in the resonance mass range from 260 to 1200 GeV.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics; HIERARCHY; MASS